Analisis Produksi Pada Industri Pabrik Tahu Alami Di Lubuk Buaya - Vivi Nila Sari; Maya Putri Zalianti; Elsida Yohani; Nur Adila; Widyanti Putri (Universitas 17 Agustus 1945 Semarang, 2023)
Tofu is a characteristic of Indonesian food, so it is not uncommon for this tofu food to be found in Padang. Tofu is a food made from soybeans, and the process is still simple and limited to household scale. Suryanto (in Hartaty, 1994) states that what is meant by tofu is solid food printed from soymilk (Glycinespp) by a protein deposition process at its isoelectric point, without or with the addition of other permitted substances. The production process of tofu starts from washing, grinding, and pressing which are carried out by humans as well as machines. The purpose of this study is to obtain alternative production strategies that can be applied in Tofu Factory Industry SMEs. The stages of this research are Preparation, Screening, Activity Implementation, Activity Evaluation